Commonly used reference values underestimate oxygen uptake in healthy, 50‐year‐old Swedish women - Genberg, M.; Andrén, B.; Lind, L.; Hedenström, H.; Malinovschi, A. (Clinical physiology and functional imaging, 2018)
Summary Cardiopulmonary exercise testing (CPET) is the gold standard among clinical exercise tests. It combines a conventional stress test with measurement of oxygen uptake (VO2) and CO2 production. No validated Swedish reference values exist, and reference values in women are generally understudied. Moreover, the importance of achieved respiratory exchange ratio (RER) and the significance of breathing reserve (BR) at peak exercise in healthy individuals are poorly understood. We compared VO2 at maximal load (peakVO2) and anaerobic threshold (VO2@AT) in healthy Swedish individuals with commonly used reference values, taking gender into account. Further, we analysed maximal workload and peakVO2 with regard to peak RER and BR. In all, 181 healthy, 50‐year‐old individuals (91 women) performed CPET. PeakVO2 was best predicted using Jones et al. (100·5%). Furthermore, underestimation of peakVO2 in women was found for all studied reference values (P<0·001) and was largest for Hansen‐Wasserman: women had 115% of predicted peakVO2, while men had 103%. PeakVO2 was similar in subjects with peak RER of 1–1·1 and RER > 1·1 (2 328·7 versus 2 176·7 ml min−1, P = 0·11). Lower BR (≤30%) related to significantly higher peakVO2 (P<0·001). In conclusion, peakVO2 was best predicted by Jones. All studied reference values underestimated oxygen uptake in women. No evidence for demanding RER > 1·1 in healthy individuals was found. A lowered BR is probably a normal response to higher workloads in healthy individuals.